SAMHD1 acetylation enhances its deoxynucleotide triphosphohydrolase activity and promotes cancer cell proliferation - Lee, Eun Ji (Oncotarget, 2017)
SAM domain and HD domain containing protein 1 (SAMHD1) is a deoxynucleotide triphosphohydrolase (dNTPase) that inhibits retroviruses by depleting intracellular deoxynucleotide triphosphates (dNTPs) in non-cycling myeloid cells. Although SAMHD1 is expressed ubiquitously throughout the human body, the molecular mechanisms regulating its enzymatic activity and function in non-immune cells are relatively unexplored. Here, we demonstrate that the dNTPase activity of SAMHD1 is regulated by acetylation, which promotes cell cycle progression in cancer cells. SAMHD1 is acetylated at residue lysine 405 (K405) in vitro and in vivo by an acetylatransferase, arrest defective protein 1 (ARD1). Acetylated SAMHD1 wildtype proteins have enhanced dNTPase activity in vitro, whereas non-acetylated arginine substituted mutants (K405R) do not. K405R mutant expressing cancer cells have reduced G1/S transition and slower proliferation compared to wildtype. SAMHD1 acetylation levels are strongest during the G1 phase, indicating a role during G1 phase. Collectively, these findings suggest that SAMHD1 acetylation enhances its dNTPase activity and promotes cancer cell proliferation. Therefore, SAMHD1 acetylation may be a potent therapeutic target for cancer treatment.